Sulfonamides incorporating heteropolycyclic scaffolds show potent inhibitory action against carbonic anhydrase isoforms I, II, IX and XII. Issue 4 (15th February 2016) - Barresi, Elisabetta; Salerno, Silvia; Marini, Anna Maria; Taliani, Sabrina; La Motta, Concettina; Simorini, Francesca; Da Settimo, Federico; Vullo, Daniela; Supuran, Claudiu T.
Graphical abstract: Abstract: Three series of polycyclic compounds possessing either primary sulfonamide or carboxylic acid moieties as zinc-binding groups were investigated as inhibitors of four physiologically relevant CA isoforms, the cytosolic hCA I and II, as well as the transmembrane hCA IX and XII. Most of the new sulfonamides reported here showed excellent inhibitory effects against isoforms hCA II, IX and XII, but no highly isoform-selective inhibition profiles. On the other hand, the carboxylates selectively inhibited hCA IX ( K I s ranging between 40.8 and 92.7 nM) without inhibiting significantly the other isoforms. Sulfonamides/carboxylates incorporating polycyclic ring systems such as benzothiopyranopyrimidine, pyridothiopyranopyrimidine or dihydrobenzothiopyrano[4, 3- c ]pyrazole may be considered as interesting candidates for exploring the design of isoform-selective CAIs with various pharmacologic applications.